Characterization of rehydrated sorghum and corn grain silages with enzymes and a model of starch ruminal degradability in feedstuffs - Fernandes, Tatiane (2018)
Paper 1. The objectives of this study were to evaluate the effect of two amyloglucosidases and duration of storage of sorghum or corn kernel rehydrated and ensiled. Kernels were rehydrated (65% of DM) before ensiled. Dosages of amyloglucosidase AMG (AMG, Novozymes) and GAM (Sanferm Yield, Novozymes) were 0.35 mL/kg of kernel. Treatments were a 2 x 3 x 2 factorial combination of G (Sorghum vs. Corn), A (CTL vs. AMG vs. GAM), and duration (30 d vs. 180 d) with 6 replicates. The in situ DM degradation was evaluated with incubation times of 0 (bag wash), 3, 6, 12, 18, and 48 h in 3 rumen cannulated cows. Rehydration and ensiling of sorghum or corn with addition of amyloglucosidase resulted in adequate fermentation, as evidenced by pH and lactic acid concentration. Increased DM loss, hydrolyze of starch, and the proportion of DM as fraction A, without alteration on kd or ERD 6.5. Is necessary long time of fermentation to improve DM digestibility. Paper 2. The objective of this study was to identify microorganism diversity and relationship between those microorganisms with characteristics of rehydrated sorghum or corn silages with addition of amyloglucosidase. For silage were used the same procedure of paper 1. Matrix-assisted laser desorption/ ionization time-of-flight mass spectrometry and PCR-based to identification. Seven species of lactic acid bacteria (LAB) were isolated with an average population of 5.74 and 3.84 ufc/g at 30 and 180 days of fermentation, respectively. The spore forming aerobic bacteria (SAB) diversity was 20 species, with an average population of of 3.18 and 2.72 ufc/g at 30 and 180 days of fermentation, respectively. The population of LAB and most part of SAB were corelated with acids and nutrient losses and negatively correlation with pH, DM and starch content. Three SAB were corelated with prolamin content. The fermentation of rehydrated kernel was dominating by LAB, with highly population, but had greater diversity of SAB. The most part of microorganisms were involved in acids production, DM and starch losses. Paper 3. The objectives of this study were to determine: 1) the most adequate method to estimate the rapidly degradable fraction (A); 2) a time-point to measure the undigestible fraction (C); and 3) the viability of using fewer time-points to estimate starch fractional disappearance rate (kd) of mature corn grain ground through 4 grinding sizes (1, 2, 4, and 6-mm). Fraction A was determined by six different procedures. Ruminal in situ incubations were performed at 48, 72, 96, and 120 h to determine fraction C, and at 0 (washing machine), 3, 6, 12, 18, 24, and 48 h to determine the kinetics of starch disappearance. Models were used with either 2 or 3-pools and kd was determined by the linear slope of the ‘ln’ of bag residues as a proportion of incubated samples over time. Fraction A was affected by grinding size; but not by washing method. Samples ground at 6-mm had greater fraction C than other grinding sizes at 48, 72 or 96 h; but not at 120 h. Model affected fraction B values solely. Greater fractions B and C, but reduced kd and ERD were observed as grinding size increased. Based on correlation analysis the 2-pool model, and the incubation times of 0, 3, and 48 h were suitable to evaluate ruminal starch degradation kinetics in feedstuffs. Ruminal in situ incubation at 120 h highlighted the lack of a fraction C of starch (0.13% of starch). Determination of fraction A by rinsing in a washing machine, and ruminal in situ incubations of 0, 3, and 48 h for starch degradation kinetics using a 2-pool model are suggested for starchy feedstuffs. Grinding size affected starch degradation kinetics.